THE IMPLEMENTATION OF CLUSTERING TECHNIQUE IN LEARNING WRITING DESCRIPTTIVE TEXT AT 8TH GRADE OF SMP N 5 RANOYAPO - Yopie A.T. Pangemanan; Jane E. Scipio; James Ed. Lalira; Morshe E. Lumansik; Barrylyn S.H. Kussoy (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
The purpose of this research is to find out 1) whether there is a significant increase in students' ability to write texts with clustering techniques, and 2) any difficulties that are associated with students in using clustering techniques. The test used is a test writing descriptive text and questionnaires. The method in this research is Post-Test Pre-Test Unit Design. The research design uses one class as an experimental class which gets two consultations using the Clustering technique. The sample used was 20 students in class VIII SMP N 5 Ranoyapo. Research data were collected through pre-test, post-test and questionnaire. The results showed a difference between pre-test and post-test statistics after the application of clustering techniques with significance values. Furthermore, most students find it difficult to use adjectives and develop main topics when using grouping techniques to write descriptive paragraphs. This shows the grouping technique makes it easy for students to improve their writing skills